Student’s and Teacher Perceptions on Online Learning and the Interrelation Between Self Efficacy and Student’ Concepts Mastery - Sari, Vivi Kurnia; Lengkana, Dewi; Yolida, Berti (Universitas Lampung, 2023)
The transition of the process of teaching and learning activities from face-to-face learning systems to online learning systems certainly provides significant changes. Online learning requires students to be more active in learning activities because teachers cannot monitor their learning process directly. This study aims to determine teacher and student perceptions, self-efficacy, concept mastery, and the interrelation between self-efficacy and conceptual mastery students of class X MIPA in online learning. The design used is descriptive quantitative with a correlational approach. The research sample consisted of 3 biology teachers and 118 students of class X MIPA SMA Negeri 1 Seputih Surabaya which were sampled from the population using total sampling technique. The research was carried out in June of the even semester of 2021. Quantitative data in the form of mastery of class X students' concepts of environmental change were obtained using questions, while qualitative data in the form of teacher perceptions, student perceptions, and student self-efficacy used a questionnaire in the form of google form. Data on perception, self-efficacy and concept mastery were analyzed descriptively, while the correlation between self-efficacy and concept mastery was analyzed inferentially with Product Moment. The results showed that the teacher's perception was categorized as good (67.28%). Students' perceptions are categorized as good (69.71%). Self-efficacy of students in the high category (67.87%). Mastery of concepts in the high category (39%). There is a positive relationship between self-efficacy and mastery concept of class X MIPA SMA Negeri 1 Seputih Surabaya with a low degree of relationship. DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27394